Anti-MuSK myasthenia gravis presenting with Epstein-Barr virus-associated mononucleosis and immune-mediated diabetes mellitus. - Bhibhatbhan, A; Kline, G; Vincent, A; Toth, C (2007)
We report a young woman with the abrupt onset of infectious mononucleosis due to Epstein-Barr virus associated with a subsequent autoimmune form of diabetes mellitus and myasthenia gravis with anti-muscle-specific kinase (MuSK) antibodies. The simultaneous onset of these two autoimmune diseases preceded by a systemic viral illness supports a causal relationship between MuSK antibodies and myasthenia gravis and suggests the possibility of a viral trigger in some cases.